Chemical composition of the essential oil of Eriobotrya japonica (Thunb.) Lindl. flowers in the western Mediterranean area - Merle H.; Boira H. (First international symposium on loquat, 2003)
The volatile oil fraction obtained from fresh flowers of Eriobotrya japonica (Thunb.) Lindl. (Rosaceae) was subject to GC-MS analysis. Thirty different compounds representing more than 95 percent of the essential oil were identified on account of their mass spectra and Retention Index (RI) values. An evaluation of yield in essential oil from fresh flowers was also carried out.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)